Design Thinking and Learning Material Utilisation Creativity in Early Childhood Teacher Education: A Case of Kyambogo University, Uganda - Katungi, Juma; Ejuu, Godfrey; Lubaale, Grace (African Journal of Education, Science and Technology, 2023)
In the recent past, we have seen a lot of innovations in children’s learning materials, equipment and spaces design due to the work of famous educators like Montessori, 1912 and Froebel, 1837. This has led to the development of a new landscape of how children’s learning spaces look like. Many children’s learning centers have heavily invested in spaces design and space equipment but despite all these developments, teachers in Uganda have registered limited success in the utilization of these facilities to enrich children’s learning experiences. This study was carried out to investigate how design thinking can be used to impact teaching spaces utilization creativity (Pacini-Ketchabaw, 2016; Hakim, 2017 & Masoumi, 2020). A Quasi-experimental with a mixed design approach was used with an embedded Pretest Post-test Design (Bhattacherjee, 2012). Quantitative and qualitative data was collected from a sample of a cohort of 64 in-service teachers studying a diploma in early childhood teacher education. Data was collected using observations, focused group interviews, and entries from the field notes. Using the Art world design thinking process, an experiment was developed to induce material utilization creativity. Alongside was a creativity observation to measure creativity indicators. This was used to measure creativity exhibited at pretest and posttest in both the control and experimental group. Data analysis used descriptive statistics for preliminary analysis and an independent group’s t-test for analyzing the difference between the control and experimental group. Findings showed that there was a statistically significant difference between the control and experimental group at post-test; this was attributed to the art world design thinking process.
Keywords: Teaching Spaces Creativity; Art world Design Thinking Process; Pedagogical Creativity; Childhood Education and Early Childhood Teacher Education